Strategi Pengembangan Nilai ke-Islaman bagi Siswa SMPIT Cordova Samarinda - Ismail Ismail; Achmad Ruslan Afendi; Anwaril Hamidy (Departement of Mathematics Education, 2023)
Abstract This research is to find out the strategy for developing Islamic values ​​carried out by SMPIT Cordova Samarinda. The type of research used is descriptive qualitative research. Data collection techniques using observation, interviews and documentation. Based on the results of the research, there is a strategy developed by the school in developing Islamic values ​​in students. Namely, the implementation of sunnah fasting, hours of habituation (monitoring children's activities during recess), reciting Al-Matsurat remembrance, mentoring, dhuha prayers, midday and afternoon prayers in congregation at school, getting used to sunnah prayers, carrying out Mabit (Night of Building Faith and Piety) and through motivational or reminder writings that are pasted or posted in certain places. As well as those who play an active role in the process of developing Islamic values ​​for SMPIT Cordova Samarinda students are all school teachers and even all school residents from teachers, administrative staff, security guards, canteen guards and cleaners also play an active role